Membuat Dan Mengembangkan Algoritma Pemrograman Untuk Edukasi Android - Fahri Rahmadsyah; Yahfizham Yahfizham (LPPM Politeknik Pratama, 2024)
The digital era of Society 5.0 has given birth to technologies which are currently showing important developments. To present a new image of Indonesian education through implementing a curriculum that is in line with the current curriculum, this technology really needs education. To get the best results from teaching and learning activities, you need to know the current learning concepts. During the learning process, this is one of the things that attracts students' attention. Additionally, as technology advances, more and more students are using smartphones, resulting in a decreased desire for physical books among today's students. In schools that still teach computer science, learning activities still use physical books provided by the government. Students thus lose interest in learning algorithms and programming and are unable to understand the topics taught. This research uses Hannafin and Peck's research approach using Website 2 APK Build and Ispring Suite 10 as the product software. This research has produced an Android-based programming algorithm learning media product through black-box testing which shows that the product created has performance according to its intended purpose and is very good for use in the educational process.